(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
My hypothesis is that landscape is identified by the atmospheric feeling it radiates in a now constant and now more ephemeral way and by the felt-bodily resonance it generates in those who simply perceive it, and a fortiori in those who are also deeply affectively grasped by it. In partial contrast to a reductionist approach prevalent today, the intention is to demonstrate that the (feeling of) landscape, in its constitutive extraneousness to the objective-quantitative dimension, can never be fully explained in pragmatist and socio-constructivist terms. In fact, it holds and even enhances its critical role if its fundamental affordance remains that of allowing a ‘contemplative’ (in the broadest sense) perspective, i.e. a involuntary, distanced, supervenient as well as ‘framed’ by boundaries perception. Precisely in questioning its boundaries, how it extends exactly as far as you feel its inherent atmosphere, the paper sketches in conclusion a liminology of the landscape on an atmospherological basis.